2023
DOI: 10.25298/2221-8785-2023-21-2-167-171
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Open Surgical Interventions for Inguinal Hernias in Elderly Patients

Abstract: Purpose. To evaluate the effectiveness of open methods of surgical treatment of inguinal hernia in elderly patients. Material and methods. The study includes 336 elderly patients with inguinal hernias. The Bassini hernioplasty was performed on 106 patients, the Liechtenstein technique was applied to 110 patients and the new tension-free method – to 120 patients. The effectiveness of hernioplasty was evaluated according to the results of the examination of patients in the early and remote postoperative periods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…For instance, Zhuk S. A., Smotrin S. M. (2023), evaluating the effectiveness of different methods of inguinal hernioplasty in elderly patients (336 patients with inguinal hernias aged 60 to 75 years), concluded that the most frequent postoperative complications were inflammatory infiltrate in the area of the postoperative wound, wound suppuration, mesh endoprosthesis rejection, hematoma in the area of surgery, testicular edema, and hernia recurrence, which differs from our results. At the same time, the authors analyzed several methods, including the Lichtenstein method (used by us), but did not study the effect of anesthesia or the dynamics of the FI, which, in our opinion, is some limitation of this study [14].…”
Section: Resultsmentioning
confidence: 98%
“…For instance, Zhuk S. A., Smotrin S. M. (2023), evaluating the effectiveness of different methods of inguinal hernioplasty in elderly patients (336 patients with inguinal hernias aged 60 to 75 years), concluded that the most frequent postoperative complications were inflammatory infiltrate in the area of the postoperative wound, wound suppuration, mesh endoprosthesis rejection, hematoma in the area of surgery, testicular edema, and hernia recurrence, which differs from our results. At the same time, the authors analyzed several methods, including the Lichtenstein method (used by us), but did not study the effect of anesthesia or the dynamics of the FI, which, in our opinion, is some limitation of this study [14].…”
Section: Resultsmentioning
confidence: 98%